Phosphorus-doped nanocarbon material and its preparation method and application

By using phosphorus-doped nanocarbon materials as the negative electrode material of lithium ion capacitors, the problems of low specific capacity and poor cycle stability in the prior art are solved, and higher specific capacity and better cycle stability are achieved, and the needs of higher energy density and longer life are met.

CN116031075BActive Publication Date: 2025-04-01CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111256306.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-27
Publication Date
2025-04-01
Estimated Expiration
2041-10-27

AI Technical Summary

Technical Problem

The existing lithium-ion capacitor negative electrode materials have low specific capacity and poor cycle stability, which cannot meet the needs of higher energy density and longer life.

Method used

The phosphorus-doped nanocarbon material is used as the negative electrode material of the lithium ion capacitor. The preparation method includes providing a uniform solution of nickel salt, a multivariate organic acid, a phosphorus source and a solvent, and then sintering and acid contact reaction after removing the solvent to obtain a phosphorus-doped nanocarbon material with a porous sheet structure and a mesoporous structure.

Benefits of technology

The specific capacity and cyclic stability of the negative electrode material of lithium ion capacitors have been improved. The specific capacity exceeds 905mAh/g at a current density of 0.1A/g, and the specific capacity exceeds 445mAh/g at 1A/g, and the specific capacity remains above 260mAh/g at 2A/g, and cycling for 500 cycles at a current density of 1A/g, with almost no attenuation and the Coulomb efficiency exceeding 99%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116031075B_ABST
    Figure CN116031075B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical energy storage, and discloses a phosphorus-doped nanocarbon material and a preparation method and application thereof. The phosphorus-doped nanocarbon material has a porous sheet structure, containing micropores and mesopores; its BET total specific surface area is 600-1500m 2 / g, the proportion of micropore specific surface area to total specific surface area is less than 20%; the total pore volume is 3‑6cm 3 / g, the proportion of micropore volume to total pore volume is less than 15%; the molar percentage of carbon on the surface of the nanocarbon material is 70-95%, and the molar percentage of phosphorus is 0.01-0.5% as measured by X-ray photoelectron spectroscopy. The negative electrode of the lithium ion capacitor containing the phosphorus-doped nanocarbon material exhibits high specific capacity and excellent cycle stability. The lithium ion supercapacitor composed of the negative electrode of the lithium ion capacitor and the commercial activated carbon YP-50F positive electrode has a high energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a phosphorus-doped nano-carbon material and a preparation method thereof, a negative electrode material for a lithium ion capacitor, a negative electrode for a lithium ion capacitor and a preparation method thereof, and a lithium ion capacitor. Background Art

[0002] With the depletion of fossil energy and the intensification of environmental problems, in order to ensure sustainable development, new energy has become a global focus. Energy storage devices including lithium-ion batteries, supercapacitors, fuel cells, etc. have been widely studied. As an important supplement to supercapacitors and lithium-ion batteries, lithium-ion capacitors have made great progress in recent years. Lithium-ion capacitors not only have higher energy density than traditional double-layer capacitors, but also have higher power density than lithium-ion batteries, which can meet the application of more scenarios. At present, the positive electrode material of lithium-ion capacitors is mainly capacitive activated carbon, which has very excellent rate performance. The negative electrode is concentrated in the negative electrode material of lithium-ion batteries, including natural graphite, artificial graphite and other materials. Unlike lithium-ion batteries, lithium-ion capacitors have higher requirements for the rate performance of the negative electrode, so as to achieve kinetic matching between the positive and negative electrodes and obtain higher power density. At the same time, the capacity and cycle stability of the negative electrode material also have a great influence on the overall energy density and life of the lithium-ion capacitor. Although graphite materials have excellent conductivity, their specific capacity and cycle life cannot meet the requirements of lithium-ion capacitors with higher energy density and longer life.

[0003] In response to the problems of graphite materials, porous carbon materials are gradually used in the negative electrode of lithium ion capacitors. Thanks to the multi-level pore structure and more active sites, it is not only conducive to the transmission of electrolyte ions but also has a higher specific capacity. In addition, the incorporation of heteroatoms can further enhance the electrochemical activity of the material. Therefore, combining the porous structure with doping can effectively improve the overall performance of the material. At present, there are many studies on nitrogen and sulfur doped carbon materials. Although phosphorus doped carbon materials have also been reported, their application in lithium ion capacitors is less. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of low specific capacity and poor cycle stability of lithium ion capacitor negative electrode materials in the prior art, and to provide phosphorus-doped nanocarbon materials and preparation methods thereof, lithium ion capacitor negative electrode materials, lithium ion capacitor negative electrodes and preparation methods thereof, and lithium ion capacitors, so as to improve the specific capacity and cycle stability of lithium ion capacitor negative electrode materials.

[0005] In order to achieve the above object, the present invention provides a phosphorus-doped nanocarbon material in a first aspect. The nanocarbon material has a porous sheet structure and contains micropores and mesopores. The total BET specific surface area of ​​the nanocarbon material is 600-1500m2 / g, the proportion of micropore specific surface area to total specific surface area is less than 20%; the total pore volume is 3-6cm 3 / g, the proportion of micropore volume to total pore volume is less than 15%; the molar percentage of carbon on the surface of the nano-carbon material measured by X-ray photoelectron spectroscopy is 70-95%, and the molar percentage of phosphorus is 0.01-0.5%.

[0006] A second aspect of the present invention provides a method for preparing a phosphorus-doped nanocarbon material, the method comprising:

[0007] (1) providing a homogeneous solution containing a nickel salt, a polybasic organic acid, a phosphorus source and a solvent, and then removing the solvent from the homogeneous solution to obtain a precursor; wherein the molar ratio of the nickel salt, the polybasic organic acid and the phosphorus source calculated on the basis of nickel element is 1:0.5-1:1-1.5;

[0008] (2) sintering the precursor under the protection of an inert atmosphere to obtain a primary product;

[0009] (3) contacting the primary product with an acid for reaction, and then performing solid-liquid separation.

[0010] The third aspect of the present invention provides a phosphorus-doped nano-carbon material prepared by the method described in the second aspect.

[0011] The fourth aspect of the present invention provides a negative electrode material for a lithium ion capacitor, wherein the negative electrode material contains an active substance, a conductive agent and a binder, and the active substance is the phosphorus-doped nanocarbon material described in the first aspect or the third aspect.

[0012] A fifth aspect of the present invention provides a negative electrode for a lithium ion capacitor, the negative electrode comprising a current collector and an electrode material coated and / or filled on the current collector, the electrode material being the negative electrode material for a lithium ion capacitor as described in the fourth aspect.

[0013] The sixth aspect of the present invention provides a method for preparing a negative electrode of a lithium ion capacitor, the preparation method comprising coating and / or filling a slurry containing an active substance, a conductive agent, an adhesive and a solvent on a current collector, drying, and rolling or not rolling, wherein the active substance is the phosphorus-doped nanocarbon material described in the first aspect or the third aspect.

[0014] The seventh aspect of the present invention provides a lithium ion capacitor, which includes a pole core and an electrolyte, wherein the pole core and the electrolyte are sealed in a battery casing, the pole core includes a positive electrode, a negative electrode and a separator, and the negative electrode is the negative electrode of the lithium ion capacitor described in the fifth aspect or is the negative electrode of the lithium ion capacitor prepared according to the preparation method described in the sixth aspect.

[0015] Through the above technical solution, the phosphorus-doped nanocarbon material provided by the present invention has a porous sheet structure, and the nanocarbon material contains micropores and mesopores; the total BET specific surface area of ​​the nanocarbon material is 600-1500m 2 / g, the proportion of micropore specific surface area to total specific surface area is less than 20%; the total pore volume is 3-6cm 3 / g, the proportion of micropore volume to total pore volume is less than 15%; the molar percentage of carbon on the surface of the nanocarbon material is 70-95%, and the molar percentage of phosphorus is 0.01-0.5% as measured by X-ray photoelectron spectroscopy. The negative electrode of the lithium ion capacitor made using the phosphorus-doped nanocarbon material exhibits a high specific capacity and excellent cycle stability. At a current density of 0.1A / g, the specific capacity exceeds 905mAh / g, and when the current density is increased to 1A / g, the specific capacity can still be maintained above 445mAh / g. In addition, at a current density of 2A / g, the specific capacity can still be maintained above 260mAh / g; after 500 cycles at a current density of 1A / g, the capacity has almost no attenuation, and the coulombic efficiency exceeds 99%. The lithium-ion supercapacitor composed of the lithium-ion capacitor negative electrode made of the phosphorus-doped nanocarbon material and the commercial activated carbon YP-50F positive electrode has a high energy density. At a power density of 112.5W / kg, the energy density exceeds 130Wh / kg; when the power density reaches 2250W / kg, the energy density can still be maintained at 75Wh / kg. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a transmission electron microscope image of the phosphorus-doped nanocarbon material prepared in Preparation Example 1;

[0017] Figure 2 is the nitrogen adsorption-desorption curve of the phosphorus-doped nanocarbon material prepared in Preparation Example 1;

[0018] Figure 3 is the Raman curve of the phosphorus-doped nanocarbon material prepared in Preparation Example 1;

[0019] Figure 4 is the rate performance curve of the negative electrode of the lithium ion capacitor prepared in Example 1;

[0020] Figure 5 is the cycle stability curve of the negative electrode of the lithium ion capacitor prepared in Example 1;

[0021] Figure 6 is the rate performance curve of the negative electrode of the lithium ion capacitor prepared in Example 2;

[0022] Figure 7 is the cycle stability curve of the negative electrode of the lithium ion capacitor prepared in Example 2;

[0023] Figure 8 is the charge and discharge curve of the button-type lithium ion capacitor prepared in Test Example 2;

[0024] Fig. 9 This is the relationship curve between the power density and energy density of the button-type lithium-ion capacitor prepared in Test Example 2. DETAILED DESCRIPTION

[0025] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0026] The first aspect of the present invention provides a phosphorus-doped nanocarbon material, wherein the nanocarbon material has a porous sheet structure, and the nanocarbon material contains micropores and mesopores; the total BET specific surface area of ​​the nanocarbon material is 600-1500m 2 / g, the proportion of micropore specific surface area to total specific surface area is less than 20%; the total pore volume is 3-6cm 3 / g, the proportion of micropore volume to total pore volume is less than 15%; the molar percentage of carbon on the surface of the nano-carbon material measured by X-ray photoelectron spectroscopy is 70-95%, and the molar percentage of phosphorus is 0.01-0.5%.

[0027] According to some embodiments of the present invention, the nano-carbon material has a porous sheet structure, and the nano-carbon material contains micropores and mesopores.

[0028] In the present invention, the term "mesopore" is defined as a pore with a pore size in the range of 2-50 nm; and "micropore" is defined as a pore with a pore size less than 2 nm.

[0029] According to some embodiments of the present invention, the surface morphology of the material is characterized by high-resolution transmission electron microscopy (HRTEM). The model of the high-resolution transmission electron microscope used is JEM-2100 (JEOL Ltd.), and the test conditions of the high-resolution transmission electron microscope are: the acceleration voltage is 200 kV.

[0030] According to some embodiments of the present invention, the total BET specific surface area of ​​the nanocarbon material is 600-1500 m 2 / g, the proportion of micropore specific surface area to total specific surface area is less than 20%. Preferably, the total BET specific surface area of ​​the nanocarbon material is 700-1000m 2 / g, the proportion of micropore specific surface area to total specific surface area is 5-15%.

[0031] According to some embodiments of the present invention, the total pore volume of the nanocarbon material is 3-6 cm 3 / g, the proportion of micropore volume to total pore volume is less than 15%. Preferably, the total pore volume of the nano-carbon material is 3.5-5.5cm 3 / g, and the proportion of micropore volume to total pore volume is 6-10%.

[0032] According to some embodiments of the present invention, the pore structure properties of the material are detected by the BET test method. Specifically, the specific surface area and pore volume of the material are obtained by the Brunauer-Emmett-Taller (BET) method, the mesopore distribution curve is calculated by the Barrett-Joyner-Halenda (BJH) method for the desorption curve, and the micropore pore size distribution curve is calculated by the Horvath-Kawazoe (HK) method for the isotherm curve.

[0033] According to some embodiments of the present invention, the molar percentage of carbon in the nano-carbon material measured by X-ray photoelectron spectroscopy is 70-95%, and the molar percentage of phosphorus is 0.01-0.5%. Preferably, the molar percentage of carbon in the nano-carbon material measured by X-ray photoelectron spectroscopy is 85-95%, and the molar percentage of phosphorus is 0.05-0.2%.

[0034] According to some embodiments of the present invention, preferably, the nano-carbon material may also contain oxygen element, which may be oxygen element in various forms formed in the phosphorus-doped nano-carbon material during the preparation process of the phosphorus-doped nano-carbon material; more preferably, the molar percentage of oxygen in the nano-carbon material measured by X-ray photoelectron spectroscopy is 5-15%, preferably 5-12%.

[0035] According to some embodiments of the present invention, X-ray photoelectron spectroscopy (XPS) analysis was performed on an ESCALab250 X-ray photoelectron spectrometer equipped with Thermo Avantage V5.926 software from Thermo Scientific, with an excitation source of monochromatic Al Kα X-rays, an energy of 1486.6 eV, a power of 150 W, a narrow scan with a penetration energy of 30 eV, and a basic vacuum of 6.53 × 10 -9 mbar, the electron binding energy was calibrated with the C1s peak (284.6 eV) of elemental carbon, data processing was performed on Thermo Avantage software, and the sensitivity factor method was used for quantitative analysis in the analysis module. Before the material was tested, it was dried in a helium atmosphere at 150°C and 1 standard atmosphere for 3 hours.

[0036] According to some embodiments of the present invention, the nano-carbon material may contain doping elements that are known to those skilled in the art and can be applied to carbon materials. Preferably, the nano-carbon material does not contain elements such as nickel, sulfur, nitrogen, boron, fluorine, chlorine, bromine, and iodine.

[0037] According to some embodiments of the present invention, preferably, in the Raman curve of the nanocarbon material, the intensity ratio of the D peak to the G peak is 0.8-1.2, preferably 0.9-1.1. In the Raman curve of the nanocarbon material, the intensity ratio of the D peak to the G peak is 1 D / I G The nano-carbon material has obvious D peak and G peak and has a high degree of graphitization.

[0038] According to some embodiments of the present invention, the Raman test adopts a visible laser Raman measurement method, which uses a 532 light source to perform Raman characterization on the functional groups of the material to provide a characteristic spectrum.

[0039] A second aspect of the present invention provides a method for preparing a phosphorus-doped nanocarbon material, the method comprising:

[0040] (1) providing a homogeneous solution containing a nickel salt, a polybasic organic acid, a phosphorus source and a solvent, and then removing the solvent from the homogeneous solution to obtain a precursor; wherein the molar ratio of the nickel salt, the polybasic organic acid and the phosphorus source calculated on the basis of nickel element is 1:0.5-1:1-1.5;

[0041] (2) sintering the precursor under the protection of an inert atmosphere to obtain a primary product;

[0042] (3) contacting the primary product with an acid for reaction, and then performing solid-liquid separation.

[0043] According to some embodiments of the present invention, the method for preparing phosphorus-doped nanocarbon materials uses a phosphorus source as a raw material and activator for providing phosphorus atoms, and simultaneously cooperates with nickel salts and polybasic organic acids to prepare complex precursor materials. By controlling the proportion of the raw materials and combining sintering and acid contact reactions, the preparation of phosphorus-doped nanocarbon materials can be simply and efficiently achieved. The prepared phosphorus-doped nanocarbon material has a porous flaky structure, a moderate specific surface area, and contains a large number of mesoporous structures.

[0044] According to some embodiments of the present invention, in step (1), there is no particular limitation on the method for forming the homogeneous solution, for example, the homogeneous solution may be formed by heating, and more preferably by heating and stirring. There is no particular limitation on the heating temperature and stirring rate, as long as the homogeneous solution can be formed.

[0045] According to some embodiments of the present invention, preferably, in step (1), the nickel salt, the polybasic organic acid and the phosphorus source are dissolved in a solvent to form the uniform solution, and then the solvent in the uniform solution is removed to obtain a precursor. There is no particular limitation on the type of the solvent, which is subject to the ability to form a uniform solution. Preferably, the solvent is water and / or ethanol, more preferably water; there is no particular limitation on the amount of the solvent, which is also subject to the ability to form a uniform solution. The solvent in the solution can be removed by drying, and the drying temperature and process can adopt the existing technology known to those skilled in the art.

[0046] According to some embodiments of the present invention, preferably, in step (1), the nickel salt is selected from one or more of nickel carbonate, basic nickel carbonate and organic acid nickel, preferably basic nickel carbonate.

[0047] According to some embodiments of the present invention, preferably, the polybasic organic acid is selected from one or more of citric acid, maleic acid, trimesic acid, terephthalic acid and malic acid, preferably citric acid.

[0048] According to some embodiments of the present invention, preferably, the phosphorus source is a potassium phosphate salt, which can be used as a raw material and an activator for providing phosphorus atoms. More preferably, the phosphorus source is selected from dipotassium hydrogen phosphate and / or potassium dihydrogen phosphate, preferably potassium dihydrogen phosphate.

[0049] According to some embodiments of the present invention, in step (1), the molar ratio of the nickel salt, polybasic organic acid and phosphorus source calculated as nickel element is 1:0.5-1:1-1.5. Preferably, the molar ratio of the nickel salt, polybasic organic acid and phosphorus source calculated as nickel element is 1:0.7-1:1-1.2. The molar ratio of the raw materials within the above preferred range is conducive to the formation of a phosphorus-doped nanocarbon material having a porous sheet structure, a moderate specific surface area and a large amount of mesoporous structure.

[0050] According to some embodiments of the present invention, in step (2), the precursor is sintered under the protection of an inert atmosphere to obtain a primary product. Preferably, the sintering conditions include: a heating rate of 1-10°C / min, preferably 5-10°C / min; a sintering temperature of 450-700°C, preferably 500-600°C; and a sintering time of 20-600min, preferably 60-240min. The sintering conditions within the above preferred range are conducive to further promoting the formation of the mesoporous structure of the phosphorus-doped nanocarbon material and further increasing its specific surface area.

[0051] According to some embodiments of the present invention, preferably, the inert atmosphere is provided by at least one of nitrogen, argon, neon and helium.

[0052] According to some embodiments of the present invention, in step (3), the primary product is contacted with an acid for reaction, and then solid-liquid separation is performed. Preferably, the step of contacting the primary product with an acid for reaction is: mixing the primary product with an acid, and there is no particular limitation on the mixing method, and the mixing can be performed by ultrasound or stirring. The acid can be an acid conventionally used in the art, as long as it can remove the nickel and potassium elements in the primary product to form a phosphorus-doped nanocarbon material having a porous sheet structure, a moderate specific surface area, and a large amount of mesoporous structure.

[0053] According to some embodiments of the present invention, preferably, the acid is an inorganic acid and / or an organic acid, preferably at least one of hydrochloric acid, sulfuric acid, nitric acid and citric acid, more preferably hydrochloric acid. More preferably, the acid is provided in the form of an aqueous solution; further preferably, in the aqueous solution of the acid, the concentration of the acid is 0.1-12 mol / L.

[0054] According to some embodiments of the present invention, preferably, the contact reaction conditions include: temperature of 40-120° C., preferably 60-100° C.; time of 4-48 h, preferably 4-12 h.

[0055] According to some embodiments of the present invention, in step (3), there is no particular limitation on the solid-liquid separation method, and the solid-liquid separation can be performed by any solid-liquid separation method known in the art, for example, solid-liquid separation can be performed by filtration.

[0056] According to some embodiments of the present invention, preferably, the solid-liquid separation further includes washing and drying steps. The washing is used to remove the acid remaining on the phosphorus-doped nano-carbon material. Therefore, various water washing methods that can wash the phosphorus-doped nano-carbon material to neutrality are applicable to the present invention. The drying is used to remove water from the phosphorus-doped nano-carbon material. Drying can be carried out by normal pressure drying or reduced pressure drying, and the drying conditions can adopt any feasible existing technology. Preferably, the drying conditions include: temperature of 100-120°C and time of 6-10h.

[0057] The third aspect of the present invention provides a phosphorus-doped nano-carbon material prepared by the method described in the second aspect.

[0058] According to some embodiments of the present invention, the nanocarbon material has a porous sheet structure, and the nanocarbon material contains micropores and mesopores; the total BET specific surface area of ​​the nanocarbon material is 600-1500m 2 / g, the proportion of micropore specific surface area to total specific surface area is less than 20%; the total pore volume is 3-6cm 3 / g, the proportion of micropore volume to total pore volume is less than 15%; the molar percentage of carbon on the surface of the nano-carbon material measured by X-ray photoelectron spectroscopy is 70-95%, and the molar percentage of phosphorus is 0.01-0.5%.

[0059] According to some embodiments of the present invention, the nano-carbon material may contain doping elements that are known to those skilled in the art and can be applied to carbon materials. Preferably, the nano-carbon material does not contain elements such as nickel, sulfur, nitrogen, boron, fluorine, chlorine, bromine, and iodine.

[0060] The fourth aspect of the present invention provides a negative electrode material for a lithium ion capacitor, wherein the negative electrode material contains an active substance, a conductive agent and a binder, and the active substance is the phosphorus-doped nanocarbon material described in the first aspect or the third aspect.

[0061] According to some embodiments of the present invention, preferably, the mass ratio of the active material, the conductive agent and the adhesive is 7-18:1-3:1, for example, it can be 9:0.5:0.5, 8:1:1, 8:1.5:0.5, 7:2:1 and any value in the range formed by any two of these values, preferably 7-15:1-2:1, and more preferably 8:1:1.

[0062] According to some embodiments of the present invention, the content and type of the conductive agent are well known to those skilled in the art. Preferably, the conductive agent is selected from one or more of acetylene black, Ketjen black, graphene and carbon nanotubes, preferably acetylene black.

[0063] According to some embodiments of the present invention, the adhesive can be any binder known in the art that can be used for lithium ion capacitors, preferably a fluorine-containing resin and / or a polyolefin compound. More preferably, the adhesive is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, polyvinyl alcohol, styrene-butadiene rubber emulsion and acrylonitrile copolymer aqueous dispersion, preferably polytetrafluoroethylene.

[0064] A fifth aspect of the present invention provides a negative electrode for a lithium ion capacitor, the negative electrode comprising a current collector and an electrode material coated and / or filled on the current collector, the electrode material being the negative electrode material for a lithium ion capacitor as described in the fourth aspect.

[0065] According to some embodiments of the present invention, preferably, the current collector is selected from a stainless steel mesh or a copper foil, preferably a stainless steel mesh.

[0066] Since the present invention only involves the improvement of the electrode active material, when the phosphorus-doped nano-carbon material of the present invention is applied to a lithium ion capacitor, there is no particular restriction on other components and structures of the lithium ion capacitor.

[0067] The sixth aspect of the present invention provides a method for preparing a negative electrode of a lithium ion capacitor, the preparation method comprising coating and / or filling a slurry containing an active substance, a conductive agent, an adhesive and a solvent on a current collector, drying, and rolling or not rolling, wherein the active substance is the phosphorus-doped nanocarbon material described in the first aspect or the third aspect.

[0068] According to a preferred embodiment of the present invention, the method for preparing the capacitor negative electrode comprises:

[0069] The phosphorus-doped nanocarbon material, the conductive agent and the adhesive are mixed, ground evenly and mixed with a solvent to form a slurry, and then the slurry is evenly coated on the current collector, dried and cut into electrode sheets.

[0070] According to another preferred embodiment of the present invention, the method for preparing the capacitor negative electrode comprises:

[0071] The phosphorus-doped nanocarbon material, the conductive agent and the adhesive are mixed, ground evenly and then mixed with a solvent to form a slurry, and the grinding is continued until the slurry is in a plasticine state. After the slurry in the plasticine state is stretched into a uniform thin sheet, it is dried, cut and pressed onto a current collector to obtain an electrode sheet.

[0072] According to some embodiments of the present invention, the solvent may be any solvent known in the art that can be used to prepare lithium ion capacitors. Preferably, the solvent is anhydrous ethanol and / or N-methylpyrrolidone, preferably anhydrous ethanol. The amount of the solvent used is based on the ability to form the desired coating slurry.

[0073] The seventh aspect of the present invention provides a lithium ion capacitor, which includes a pole core and an electrolyte, wherein the pole core and the electrolyte are sealed in a battery casing, the pole core includes a positive electrode, a negative electrode and a separator, and the negative electrode is the negative electrode of the lithium ion capacitor described in the fifth aspect or is the negative electrode of the lithium ion capacitor prepared according to the preparation method described in the sixth aspect.

[0074] According to some embodiments of the present invention, the positive electrode can be any positive electrode known in the art that can be used to prepare a lithium ion capacitor, preferably an activated carbon material with double-layer energy storage, such as commercial activated carbon YP-50F.

[0075] According to some embodiments of the present invention, the electrolyte may be any electrolyte known in the art that can be used to prepare a lithium ion capacitor. Preferably, the electrolyte is an organic electrolyte, more preferably a lithium hexafluorophosphate electrolyte.

[0076] According to some embodiments of the present invention, preferably, the battery housing is a button-type battery housing.

[0077] According to some embodiments of the present invention, the separator can be any separator known in the art that can be used to prepare lithium ion capacitors. Preferably, the separator is selected from any one of polyethylene film, polypropylene film and cellulose film, preferably polypropylene film.

[0078] According to some embodiments of the present invention, since the phosphorus-doped nano-carbon material has a porous sheet structure, a moderate specific surface area, and contains a pore structure mainly composed of mesopores, it is beneficial to the transmission of electrolyte ions, so that the lithium ion capacitor negative electrode prepared using the phosphorus-doped nano-carbon material exhibits good rate performance and cycle stability. In addition, the incorporation of phosphorus atoms and the active sites in the sheet structure make the negative electrode have excellent specific capacity.

[0079] The present invention will be described in detail below by way of examples. In the following examples and comparative examples:

[0080] The surface morphology of the material was characterized by high-resolution transmission electron microscopy (HRTEM). The model of the high-resolution transmission electron microscope used was JEM-2100 (JEOL Ltd.), and the test conditions of the high-resolution transmission electron microscope were: the acceleration voltage was 200 kV.

[0081] The pore structure properties of the material were detected by the BET test method. Specifically, the Quantachrome AS-6B analyzer was used for the determination. The specific surface area and pore volume of the material were obtained by the Brunauer-Emmett-Taller (BET) method, the mesopore distribution curve was calculated by the Barrett-Joyner-Halenda (BJH) method for the desorption curve, and the micropore size distribution curve was calculated by the Horvath-Kawazoe (HK) method for the isotherm curve.

[0082] The content of each element on the surface of the material was determined by X-ray photoelectron spectroscopy (XPS). The X-ray photoelectron spectroscopy analysis was carried out on an ESCALab250 X-ray photoelectron spectrometer equipped with Thermo Avantage V5.926 software from Thermo Scientific. The excitation source was monochromatic Al Kα X-ray with an energy of 1486.6 eV and a power of 150 W. The penetration energy used for narrow scanning was 30 eV. The basic vacuum during the analysis test was 6.53×10 -9 mbar, the electron binding energy was calibrated with the C1s peak (284.6 eV) of elemental carbon, data processing was performed on Thermo Avantage software, and the sensitivity factor method was used for quantitative analysis in the analysis module. Before the material was tested, it was dried in a helium atmosphere at 150°C and 1 standard atmosphere for 3 hours.

[0083] Raman testing uses visible laser Raman measurement method, using 532 light source to perform Raman characterization on the functional groups of the material and give a characteristic spectrum.

[0084] The electrochemical properties of the material were obtained by testing at different current densities using the CT2 001A Land battery testing system of Wuhan Blue Electric Company.

[0085] Preparation Examples 1-2 are used to illustrate phosphorus-doped nanocarbon materials and preparation methods thereof.

[0086] Preparation Example 1

[0087] Material preparation:

[0088] (1) Basic nickel carbonate, citric acid, and potassium dihydrogen phosphate (calculated as nickel element) were dissolved in an appropriate amount of deionized water in a molar ratio of 1:1:1, heated and stirred at 95° C. for 4 h, and then placed in an oven to dry to obtain a precursor.

[0089] (2) The precursor was ground into powder, and then placed in a tubular calcining furnace. Under the protection of nitrogen, the temperature was increased to 600°C at a heating rate of 5°C / min, and the mixture was calcined at a constant temperature for 2 hours. Finally, the mixture was naturally cooled to room temperature to obtain a black primary product.

[0090] (3) The initial product was dissolved in an appropriate amount of deionized water, stirred evenly, and then an excess of concentrated hydrochloric acid (concentration of 12 mol / L) was added. The temperature was then raised to 90°C and heated and stirred for 12 hours. After cooling to room temperature, the mixture was filtered and the filter cake was washed with water until it was neutral, and then placed in an oven and dried overnight to finally obtain phosphorus-doped nanocarbon material.

[0091] Basic properties characterization:

[0092] The transmission electron microscopy image of the phosphorus-doped nanocarbon material is shown in Figure 1 As shown, it can be seen from the figure that the material is a sheet-like structure.

[0093] The isothermal adsorption-desorption curves of the phosphorus-doped nanocarbon material are shown in Figure 2 As shown, the BET total specific surface area of ​​the material is 771.49 m 2 / g, the specific surface area in micropores is 58.45m 2 / g, accounting for 7.6% of the total specific surface area; the total pore volume is 3.85cm 3 / g, the proportion of micropore volume to total pore volume is 7.9%, indicating that the material is mainly mesoporous structure.

[0094] The atomic ratio of each element on the surface of the material was calculated based on the peak area of ​​X-ray photoelectron spectroscopy (XPS), wherein C was 89.11%, O was 10.84%, and P was 0.05%.

[0095] The Raman test results of the phosphorus-doped nanocarbon material are as follows Figure 3 As shown in the figure, it can be seen that the material has obvious D peak and G peak, and the intensity ratio of D peak to G peak (I D / I G ) is 0.99, indicating that the material has a certain degree of graphitization.

[0096] Preparation Example 2

[0097] Material preparation:

[0098] The method of Preparation Example 1 is followed, except that in step (2), the sintering temperature is reduced from 600° C. to 550° C., and the remaining raw materials, steps and conditions are the same as those of Preparation Example 1 to obtain phosphorus-doped nanocarbon material.

[0099] Basic properties characterization:

[0100] The phosphorus-doped nanocarbon material has a flake structure and a BET total specific surface area of ​​956.82 m 2 / g, the specific surface area in micropores is 138.79m 2 / g, accounting for 14.5% of the total specific surface area; the total pore volume is 5.001cm 3 / g, the proportion of micropore volume to total pore volume is 7.71%, indicating that the material is mainly composed of mesoporous structure.

[0101] The atomic ratio of each element on the surface of the material was calculated based on the peak area of ​​X-ray photoelectron spectroscopy (XPS), wherein C was 94.29%, O was 5.64%, and P was 0.06%.

[0102] The Raman test results of the phosphorus-doped nanocarbon material show that the intensity ratio of the D peak to the G peak (I D / I G ) is 0.98, indicating that the material has a certain degree of graphitization.

[0103] Comparative Preparation Example 1

[0104] Material preparation:

[0105] (1) Basic nickel carbonate and citric acid were dissolved in an appropriate amount of deionized water in a molar ratio of 1:1, heated and stirred at 95° C. for 4 h, and then placed in an oven to dry to obtain a precursor.

[0106] (2) The precursor was ground into powder, and then placed in a tubular calcining furnace. Under the protection of nitrogen, the temperature was increased to 600°C at a heating rate of 5°C / min, and the mixture was calcined at a constant temperature for 2 hours. Finally, the mixture was naturally cooled to room temperature to obtain a black primary product.

[0107] (3) The initial product was dissolved in an appropriate amount of deionized water, stirred evenly, and then an excess of concentrated hydrochloric acid was added. The temperature was then raised to 95°C and heated and stirred for 12 hours. After cooling to room temperature, the filter cake was washed with water until it was neutral, and then placed in an oven and dried overnight to finally obtain an undoped nanocarbon material.

[0108] Basic properties characterization:

[0109] The BET total specific surface area of ​​the nanocarbon material was calculated to be 264.96 m 2 / g, the specific surface area in micropores is 8.28m 2 / g, accounting for 3.1% of the total specific surface area; the total pore volume is 0.68cm 3 / g, and the proportion of micropore volume to total pore volume is 2%, indicating that the material is almost a fully mesoporous structure.

[0110] The atomic ratio of each element on the surface of the material can be calculated based on the peak area in the X-ray photoelectron spectroscopy (XPS), among which C is 88.42%, O is 6.34%, and Ni is 5.24%.

[0111] According to the Raman test results, the intensity ratio of the D peak and the G peak of the material (I D / I G ) is 1.00.

[0112] Example 1-2 is used to illustrate the negative electrode of a lithium ion capacitor and its preparation method

[0113] Example 1

[0114] The phosphorus-doped nanocarbon material, acetylene black, and polytetrafluoroethylene prepared in Preparation Example 1 were mixed in a mass ratio of 8:1:1, and an appropriate amount of anhydrous ethanol was dropped and fully ground until the slurry was in a plasticine state. The plasticine-like slurry was stretched and rolled into a uniform thin sheet using a glass rod, and then placed in an oven to dry at 80°C for 3 hours. After complete drying, it was cut into circular pole pieces with a diameter of 10 mm. Subsequently, a hydraulic press was used to press the circular pole piece onto the stainless steel mesh current collector at a pressure of 10 MPa to obtain a lithium ion capacitor negative electrode with the stainless steel mesh as the current collector.

[0115] Example 2

[0116] The phosphorus-doped nanocarbon material, acetylene black and polyvinylidene fluoride prepared in Preparation Example 1 were mixed in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone was dropped into the mixture. The mixture was fully ground, and then the slurry was evenly scraped onto the copper foil and dried in an oven at 80°C for 12 hours. After complete drying, the mixture was cut into circular pole pieces with a diameter of 10 mm to obtain the negative electrode of a lithium ion capacitor with the copper foil as the current collector.

[0117] Example 3

[0118] According to the method of Example 1, the difference is that the active material is replaced by the phosphorus-doped nanocarbon material prepared in Preparation Example 2, and the remaining raw materials, steps and conditions are the same as those in Example 1 to obtain a lithium ion capacitor negative electrode with a stainless steel mesh as a current collector.

[0119] Comparative Example 1

[0120] According to the method of Example 1, the difference is that the active material is replaced by the nano-carbon material prepared in Comparative Preparation Example 1, and the other raw materials, steps and conditions are the same as those in Example 1, to obtain a lithium ion capacitor negative electrode with a stainless steel mesh as a current collector.

[0121] Test Example 1

[0122] This test example is used to illustrate the electrochemical performance test of the negative electrode of a lithium-ion capacitor.

[0123] Assembly of lithium ion capacitor: The lithium ion capacitor negative electrode and polypropylene diaphragm prepared in Examples 1-3 were respectively soaked in lithium hexafluorophosphate electrolyte for 0.5 h and then taken out, and lithium hexafluorophosphate was used as the electrolyte to assemble a button-type lithium ion capacitor in the order of battery shell-lithium sheet-diaphragm-lithium ion capacitor negative electrode-battery shell.

[0124] Performance test: The button-type lithium-ion capacitors were characterized by specific capacity and rate performance using the Blue Electric system. Within the voltage range of 0-3V, they were first discharged and then charged at different current densities (0.1-2A / g).

[0125] The present invention exemplarily provides a lithium ion capacitor negative electrode prepared in Example 1, and the corresponding specific capacity at different current densities is as follows: Figure 4 As shown in the figure, the specific capacity of the negative electrode exceeds 945mAh / g at a current density of 0.1A / g, and the specific capacity decreases as the current density increases. When the current density is increased to 1A / g, the specific capacity can still reach 520mAh / g. In addition, at a current density of 2A / g, the specific capacity of 375mAh / g can still be maintained. The negative electrode exhibits very excellent cycle stability. After 500 cycles at a current density of 1A / g, the capacity has almost no attenuation, and the coulombic efficiency exceeds 99.5%. Figure 5 shown.

[0126] The present invention exemplarily provides a negative electrode of a lithium ion capacitor prepared in Example 2, and the corresponding specific capacity at different current densities is as follows: Figure 6As shown in the figure, the specific capacity of the negative electrode exceeds 905mAh / g at a current density of 0.1A / g. As the current density increases, the specific capacity decreases. When the current density is increased to 1A / g, the specific capacity can still reach 445mAh / g. In addition, at a current density of 2A / g, the specific capacity can still be maintained at 260mAh / g. The negative electrode also shows very excellent cycle stability. It cycles 500 times at a current density of 1A / g. Figure 7 As shown, the capacity hardly decays and the Coulombic efficiency exceeds 99.5%.

[0127] The negative electrode of the lithium ion capacitor prepared in Example 3 has a specific capacity of more than 1000mAh / g at a current density of 0.1A / g, and the specific capacity decreases as the current density increases. When the current density is increased to 1A / g, the specific capacity can still reach 690mAh / g. In addition, at a current density of 2A / g, the specific capacity can still be maintained at 580mAh / g. The negative electrode also shows very excellent cycle stability. It has almost no capacity decay after 500 cycles at a current density of 1A / g, and the coulombic efficiency exceeds 99%.

[0128] Comparative test example 1

[0129] The lithium ion capacitor was assembled and the performance test was performed according to the method of Test Example 1, except that the negative electrode used was the lithium ion capacitor negative electrode prepared in Comparative Example 1.

[0130] Under the same assembly and test conditions, the lithium ion capacitor negative electrode prepared in Comparative Example 1 has a stable specific capacity of only 500mAh / g at a current density of 0.1A / g. At a current density of 1A / g, the specific capacity is only 150mAh / g. When the current density is increased to 2A / g, the specific capacity is only 130mAh / g. After 500 cycles, the capacity retention rate is only 80%.

[0131] Test Example 2

[0132] This test example is used to illustrate the electrochemical performance test of button-type lithium-ion capacitors.

[0133] Assembly of lithium ion capacitor: First, the negative electrode of the lithium ion capacitor prepared in Example 1 is pre-embedded with lithium to obtain a pre-embedded lithium-phosphorus-doped negative electrode, and then lithium hexafluorophosphate is used as the electrolyte to assemble a complete button-type lithium ion capacitor in the order of battery shell-pre-embedded lithium-phosphorus-doped negative electrode-diaphragm-commercial activated carbon positive electrode (purchased from Cyber ​​Electrochemical Materials Network, model / brand Kurary YP-50F)-battery shell.

[0134] Performance test: The button-type lithium ion capacitors were characterized by the Blue Electric system for specific capacity and rate performance. In the voltage range of 0-4V, they were charged and then discharged at different current densities (0.1-2A / g).

[0135] The present invention provides illustratively the performance test results of a lithium ion capacitor composed of a lithium ion capacitor negative electrode prepared in Example 1 and a commercial activated carbon electrode, and its charge and discharge curves at different current densities are as follows: Figure 8 As shown. Using the formula: power density P = (V max +V min )*I / 2m, energy density E=P*t / 3600, calculate the relationship curve between energy density and power density of the capacitor, such as Fig. 9 As shown in the figure, the energy density of this capacitor exceeds 130Wh / kg at a power density of 112.5W / kg; when the power density reaches 2250W / kg, the energy density can still be maintained at 75Wh / kg.

[0136] It can be seen from the above results that the negative electrode of the lithium ion capacitor made of the phosphorus-doped nano-carbon material provided by the present invention shows a high specific capacity and excellent cycle stability. At a current density of 0.1A / g, the specific capacity exceeds 905mAh / g. When the current density is increased to 1A / g, the specific capacity can still be maintained above 445mAh / g. In addition, at a current density of 2A / g, the specific capacity can still be maintained above 260mAh / g; after 500 cycles at a current density of 1A / g, the capacity has almost no attenuation, and the coulomb efficiency exceeds 99%. The lithium ion supercapacitor composed of the negative electrode of the lithium ion capacitor made of the phosphorus-doped nano-carbon material and the commercial activated carbon YP-50F positive electrode has a high energy density. At a power density of 112.5W / kg, the energy density exceeds 130Wh / kg; when the power density reaches 2250W / kg, the energy density can still be maintained at 75Wh / kg.

[0137] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A phosphorus-doped nanocarbon material, characterized in that: The nano-carbon material has a porous sheet structure, and the nano-carbon material contains micropores and mesopores; the total BET specific surface area of ​​the nano-carbon material is 600-1500m 2 / g, the proportion of micropore specific surface area to total specific surface area is less than 20%; the total pore volume is 3-6cm 3 / g, the proportion of micropore volume to total pore volume is less than 15%; the molar percentage of carbon on the surface of the nano-carbon material is 70-95%, and the molar percentage of phosphorus is 0.01-0.5% as measured by X-ray photoelectron spectroscopy.

2. The phosphorus-doped nanocarbon material according to claim 1, wherein: The total BET specific surface area of ​​the nanocarbon material is 700-1000 m 2 / g, the ratio of micropore specific surface area to total specific surface area is 5-15%; And / or, the total pore volume of the nanocarbon material is 3.5-5.5 cm 3 / g, the proportion of micropore volume to total pore volume is 6-10%; And / or, measured by X-ray photoelectron spectroscopy, the molar percentage of carbon in the nano-carbon material is 85-95%, and the molar percentage of phosphorus is 0.05-0.2%.

3. The phosphorus-doped nanocarbon material according to claim 1, wherein: In the Raman curve of the nano-carbon material, the intensity ratio of the D peak to the G peak is 0.8-1.

2.

4. The phosphorus-doped nanocarbon material according to claim 3, wherein: In the Raman curve of the nano-carbon material, the intensity ratio of the D peak to the G peak is 0.9-1.

1.

5. A method for preparing the phosphorus-doped nanocarbon material according to any one of claims 1 to 4, characterized in that: The method includes: (1) providing a homogeneous solution containing a nickel salt, a polybasic organic acid, a phosphorus source and a solvent, and then removing the solvent from the homogeneous solution to obtain a precursor; wherein the molar ratio of the nickel salt, the polybasic organic acid and the phosphorus source calculated on the basis of nickel element is 1:0.5-1:1-1.5; (2) sintering the precursor under the protection of an inert atmosphere to obtain a primary product; (3) contacting the primary product with an acid for reaction, and then performing solid-liquid separation.

6. The method according to claim 5, wherein: In step (1), the nickel salt is selected from one or more of nickel carbonate, basic nickel carbonate and organic acid nickel; and / or, the polybasic organic acid is selected from one or more of citric acid, maleic acid, trimesic acid, terephthalic acid and malic acid; And / or, the phosphorus source is selected from dipotassium hydrogen phosphate and / or potassium dihydrogen phosphate; And / or, the solvent is selected from water and / or ethanol.

7. The method according to claim 6, wherein: In step (1), the nickel salt is basic nickel carbonate; And / or, the polybasic organic acid is citric acid; And / or, the phosphorus source is potassium dihydrogen phosphate; And / or, the solvent is water.

8. The method according to any one of claims 5 to 7, wherein: In step (1), the molar ratio of the nickel salt, the polybasic organic acid and the phosphorus source calculated on the basis of nickel element is 1:0.7-1:1-1.

2.

9. The method according to claim 5, wherein: In step (2), the sintering conditions include: a heating rate of 1-10°C / min; a sintering temperature of 450-700°C; and a sintering time of 20-600min.

10. The method according to claim 9, wherein: In step (2), the sintering conditions include: a heating rate of 5-10°C / min; a sintering temperature of 500-600°C; and a sintering time of 60-240min.

11. The method according to claim 5, wherein: In step (3), the contact reaction conditions include: temperature of 40-120°C; time of 4-48h; And / or, the acid is an inorganic acid and / or an organic acid.

12. The method according to claim 11, wherein: In step (3), the contact reaction conditions include: temperature of 60-100°C; time of 4-12h; And / or, the acid is one or more of hydrochloric acid, sulfuric acid, nitric acid and citric acid.

13. The method according to claim 12, wherein: In step (3), the acid is hydrochloric acid.

14. A negative electrode material for a lithium ion capacitor, comprising an active material, a conductive agent and a binder, characterized in that: The active material is the phosphorus-doped nanocarbon material according to any one of claims 1 to 4.

15. The negative electrode material for lithium ion capacitor according to claim 14, wherein: The mass ratio of the active material, the conductive agent and the binder is 7-18:1-3:1; And / or, the conductive agent is selected from one or more of acetylene black, Ketjen black, graphene and carbon nanotubes; And / or, the binder is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, polyvinyl alcohol, styrene-butadiene rubber emulsion and acrylonitrile copolymer aqueous dispersion.

16. The negative electrode material for lithium ion capacitor according to claim 15, wherein: The mass ratio of the active material, the conductive agent and the binder is 7-15:1-2:1; And / or, the conductive agent is acetylene black; And / or, the adhesive is polytetrafluoroethylene.

17. A negative electrode for a lithium ion capacitor, comprising a current collector and an electrode material coated and / or filled on the current collector, characterized in that: The electrode material is the negative electrode material for a lithium ion capacitor according to any one of claims 14 to 16.

18. The negative electrode for a lithium ion capacitor according to claim 17, wherein: The current collector is selected from stainless steel mesh or copper foil.

19. The negative electrode for a lithium ion capacitor according to claim 18, wherein: The current collector is a stainless steel mesh.

20. A method for preparing a negative electrode of a lithium ion capacitor, the method comprising coating and / or filling a slurry containing an active material, a conductive agent, a binder and a solvent on a current collector, drying, and rolling or not rolling, wherein: The active material is the phosphorus-doped nanocarbon material according to any one of claims 1 to 4.

21. The preparation method according to claim 20, wherein: The solvent is anhydrous ethanol and / or N-methylpyrrolidone.

22. The preparation method according to claim 21, wherein The solvent is anhydrous ethanol.

23. A lithium ion capacitor, comprising a core and an electrolyte, wherein the core and the electrolyte are sealed in a battery housing, the core comprising a positive electrode, a negative electrode and a diaphragm, characterized in that: The negative electrode is the negative electrode of a lithium ion capacitor according to any one of claims 17 to 19 or is the negative electrode of a lithium ion capacitor prepared by the preparation method according to any one of claims 20 to 22.

24. The lithium ion capacitor according to claim 23, wherein: The positive electrode is an activated carbon material; and / or The electrolyte is an organic electrolyte; and / or The battery housing is a button-type battery housing; and / or The separator is selected from any one of a polyethylene film, a polypropylene film and a cellulose film.

25. The lithium ion capacitor according to claim 24, wherein: The electrolyte is lithium hexafluorophosphate electrolyte; and / or The diaphragm is a polypropylene film.

Citation Information

Patent Citations

  • Boron containing porous carbon electrode material and preparation thereof

    CN101388291A

  • Functionalized Carbon Electrode, Related Material, Process for Production, and Use Thereof

    US20140113200A1